A CLINICAL EVALUATION OF JATIPHALA CHURNA LEPA IN VYANGA WSR TO MELASMA (International Journal of Ayurveda and Pharma Research, 2020)
Vyanga is the one of the Kshudra Roga, characterised by Niruja (painless), Shyava Varna Mandalas (bluish black patches) occurring especially on the face. While considering the pathogenesis of Vyanga, involvement of Pitta is more and it is Rakta Pradoshaja vyadhi. On the basis of clinical features it is correlated with melasma, or facial melanosis, one of the hyper pigmented disorders. Melasma is a common acquired hypermelanosis that affects sun- exposed areas of skin. This study is important since melasma is a disease causing mental side effects in patients, due to darkness and opacity of the skin; therefore, the treatment of melasma in terms of its psychological complication is of particular importance. Jatiphala (Myristica fragrans Houtt.) is an important drug which has got various medicinal uses. The seed and aril of Jatiphala (Myristica fragrans Houtt.) of family myristicaceae have the utilized therapeutically as medicine as well as a spice. Acharya Bhavamishra have mentioned Jatiphala (Myristica fragrans Houtt.) as a single herbal remedy for its action on Vyanga.Intervention and duration: 30 patients having hyperpigmentation on face with clinical manifestations, fulfilling the diagnostic criteria of Vyanga, the prepared Lepa churna was applied over the affected area, once a day for 60 days. Pre test assessment was done on 15th day, 30th and 60thday. Results: The subjective and objective parameters of the study were graded and the results of the study were analysed statistically using descriptive statistics where the study has shown statistically significant in the subjective and objective parameters. Conclusion: This clinical study of Jatiphala churna lepa showed the result in 50-60% of people in the group of Vyanga.